2010
DOI: 10.1016/j.neuroimage.2009.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Integration of iconic gestures and speech in left superior temporal areas boosts speech comprehension under adverse listening conditions

Abstract: Correspondence should be addressed to Henning Holle, h.holle@sussex.ac.uk, Phone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
135
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 45 publications
16
135
6
Order By: Relevance
“…Thus, these direct connections might underlie inhibitory control during perception of eye motion. Furthermore, these direct connections with left IFG nicely dovetail with fMRI findings demonstrating coactivations (Holle et al, 2010) and effective connectivity (Willems et al, 2009) of left pSTS and IFG during integration of speech and gestures. Finally, both left and right pSTS were connected with posterior parts of the ipsilateral IPL.…”
Section: Anatomical Fiber Connections Of Pstssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, these direct connections might underlie inhibitory control during perception of eye motion. Furthermore, these direct connections with left IFG nicely dovetail with fMRI findings demonstrating coactivations (Holle et al, 2010) and effective connectivity (Willems et al, 2009) of left pSTS and IFG during integration of speech and gestures. Finally, both left and right pSTS were connected with posterior parts of the ipsilateral IPL.…”
Section: Anatomical Fiber Connections Of Pstssupporting
confidence: 76%
“…No modulation by the social meaning of gaze shifts was found in left pSTS (or pMTG on either side). Accordingly, recent studies suggested that the left pSTS may process the causality of biological motion (Morris et al, 2008) and integrates biological motion with language (Holle et al, 2010;Willems et al, 2009), whereas the right pSTS is more specifically engaged by emotional and social information (Blakemore et al, 2004).…”
Section: Location and Functional Properties Of Pstsmentioning
confidence: 99%
“…The language network, together with inferior parietal cortex, is also engaged during sign language production (Emmorey et al, 2007;MacSweeney et al, 2008). Importantly, the first whole-brain pattern shows fronto-temporal areas that have repeatedly been found in studies of co-speech gesture perception, such as left inferior frontal gyrus and left superior temporal gyrus (Dick et al, 2012;Green et al, 2009;Holle et al, 2008Holle et al, , 2010Willems et al, 2007Willems et al, , 2009). In addition, these areas are associated with semantic processes, such as word retrieval (left inferior frontal gyrus: Amunts et al, 2004;de Zubicaray & McMahon, 2009;Thompson-Schill et al, 1999;Tremblay & Gracco, 2006; superior temporal gyrus: Graves et al, 2010;Heath et al, 2012;Khader et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Their coordination with speech is both temporal-kinetic and semantic (Kita & Özyürek, 2003;Loehr, 2007) and they have been shown to affect learning and memory in the listener as well as the speaker (Goldin-Meadow, 2003;Hostetter, 2011;Marstaller & Burianová, 2013). Previous neuroimaging studies have found that the observation of co-speech gestures engages superior and middle temporal gyrus, intraparietal sulcus, and inferior frontal gyrus (Dick et al, 2009;Holle et al, 2008Holle et al, , 2010Hubbard et al, 2009;Kircher et al, 2009;Skipper et al, 2007Skipper et al, , 2009Straube et al, 2011;Willems et al, 2007Willems et al, , 2009). The findings from these studies strongly suggest that during the observation of co-speech gestures, frontal and temporal regions are engaged in semantic processing, whereas frontal and parietal areas are activated for action understanding (Marstaller & Burianová, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is interesting to consider that the perisylvian region is also involved in the integration of iconic gestures and speech (Holle, Obleser, Rueschemeyer, & Gunter, 2010;Straube, Green, Bromberger, & Kircher, 2011; for reviews see also Andric & Small, 2012;Marstaller & Burianov a, 2014). Furthermore, the posterior STS has been reported to be part of the action observation network (Georgescu et al, 2014) and incorporated in a neural network activated in social interaction (Leube et al, 2012).…”
Section: Visual Exploration Behaviour In Aphasic Patientsmentioning
confidence: 99%